ANALISIS KESALAHAN BERBAHASA INDONESIA DI BIDANG WACANA DALAM IKLAN PRODUK - PRODUK INDONESIA - Restu Tomo, Dicky; Azizah Damaryanti, Dewi; Dhiya Rofifah, Oktavia; Wian Arifana , M. (Bahtera Indonesia, 2020)
The purpose of this study is to describe the mistakes of Indonesian language in the field of discourse on the advertising of products in Indonesia. The ads analyzed are food ads, drinks, beauty soaps, and others. This research uses descriptive method through two stages namely the stage of data collection and data analysis. The chosen research subject is advertising Indonesian products using written language. While the object is the analysis of errors in the Indonesian language in the field of discourse. The results obtained from this study were found 1 data referencing error usage, 2 data recovery use errors (substitution), 1 data ineffectiveness discourse because there is no impregnation, 1 data conjunction error, 1 data incoherent discourse, 2 error data that deviate from Indonesian language rules, and 2 data on force / ambiguity.